Masa Awal Dakwah Islam di Indonesia - Syamsuddin RS (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
Islam came into the Indonesian social context latter than other coexistirig religions but emanated throughout the Indonesian archipelago so faster. This rapid development was made possible by several elements. First, monotheism as the core of Islamic teachings suits the local people because it is actually the fitrah of all mankinds.Second, Islam was brought to Indonesia in such peaceful ways without any attachement to any form of colonialism. Third; Islam was proselytized in a persuasive sphere, the da'is not involving in any form of intimidation to any individual or group. Fourth, the approach used in dakwah Islam in Indonesia was a cultural one, in that it tends to appreciate the local cultures including preceding beliefs. This approach was not, however, without risk but Islam was trapped in an inevitable syncretism. Finally, Islam was politically advantaged and supported by the establishment of Islamic sultanates throughout the Indonesian archipelago.